Transparansi Anggaran Pendapatan dan Belanja Daerah di Era Pandemi Covid-19: Peran Sistem Informasi Pemerintahan Daerah - Kartika, I Gusti Ayu Yuli; Gorda, A. A. N. Eddy Supriyadinata (E-Jurnal Akuntansi; Vol 32 No 1 (2022), 2022)
Transparency in the Regional Revenue and Expenditure Budget (APBD) is one manifestation of Good Governance. This study aims to examine the effect of accessibility, internal control system, and performance-based budgeting on APBD transparency with the application of the Regional Government Information System (SIPD) as an intervening variable. This research was conducted at the Bali Province Regional Financial and Asset Management Agency (BPKAD). The research population is all civil servants in BPKAD and the sampling technique used is saturated sampling. Structural equation model is used as a data analysis tool. The results showed that the Regional Government Information System (SIPD) positively mediated the influence of accessibility, internal control systems, and performance-based budgeting on APBD transparency. Keywords :  Accessibility; Internal Control System; Performance Based Budgeting; Transparency.